PENGARUH UKURAN KAP, UKURAN PERUSAHAAN DAN AUDIT TENURE TERHADAP KUALITAS AUDIT (STUDI EMPIRIS PERUSAHAAN PERINDUSTRIAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE TAHUN 2018-2022) - Dinda, Adinda Fidiah Dwi Pratiwi; Nazar, Shinta Ningtyas (Publika Citra Media, 2025)
This study aims to analyze and obtain empirical evidence regarding the influence of cap size, company size and Tenure Audit on Audit Quality in industrial sector companies in Indonesia. The research sample is industrial companies listed on the Indonesia Stock Exchange (IDX) for the period between 2018-2022. The type of research used is quantitative research, and the type of data used is secondary data. Data collection was carried out by the purposive sampling method. The number of companies sampled was 13 companies with 65 data on financial statement and annual reports. Data processing using eviews 12 with the analysis method of this study using logistic regression. The results of this study show that based on the statistical z test, the size of the cap partially has no effect on audit quality, the size of the company partially has a significant effect on audit quality, and the tenure audit partially has no effect on audit quality. Based on the Simultaneous LR test, it shows that the size of the hood, the size of the company and the audit tenure simultaneously effect the quality of the audit